BUS TICKETS SALES DEPARTMENT RECAPITULATION KARAWACI USING VISUAL BASIC 6.0 - Rahmaniar Rahmaniar; Ir. Fitri Sjafrina, MM (Jurnal Sistem Informasi, 2004)
used as the ticket sales based decision making in the direction you have set a limit.For prospective members who want to register must submit a money amounting toRp 50,000 as initial deposit and for which already a member, every month the moneyamounted to Rp. 300.000 in which the record which still uses the traditional sorequires a long time.On application for the calculation of the recapitulation of the author there are fiveforms. On the main form, the form the bus, the form of passenger data, the ticketreservation form and cancellation of ticket data form.To the officer who made the calculation of the recapitulation, at least be able tooperate the existing windows and has the specifications of the hardware and software.